Agro-climate and intensity of the disease rot of bacteria in two planting seasons. Issue 1 (March 2021) - Fatmawati; Faisal, F; Aflaha, I; Amin, N; Baharuddin
Abstract: Bacterial grain rot caused by bacteria Burkholderia Glumae (BG), is a new disease found in South Sulawesi. Maros area as one of rice production centers began to be detected by BG attack in 2015 from the results of monitoring BBKP Makassar, but there are no further studies on the epidemiology of the disease in cropping. BBB disease can easily infect through the seeds. The spread of seedlings without the seed health test and the inclusion of the hybrid import seeds also spur the spread and malignancy of BBB disease in the field. Extreme weather changes are one of the factors that cause an explosion of the disease in various countries so that it can cause a loss of results ranged from 40-70%. This research aims to determine the agroclimatic relationship to the intensity of BBB disease. Based on the observation of the agroclimatic and the intensity of the BBB disease in Maros Regency for two planting seasons (IP 300-Rendan) shows that the dominant disease attack occurs during the rainy season (November-March) in the planting season of IP 300 and With air temperature ranging from 320 C and humidity 67%. The disease intensity of some varied varieties ranges from 17.5-73%